Developing the relational in teacher feedback literacy: exploring feedback talk. Issue 2 (17th February 2023) - Heron, Marion; Medland, Emma; Winstone, Naomi; Pitt, Edd
Abstract: The higher education literature on feedback has generally explored spoken feedback delivered on a summative written assignment. In contrast, this study explores spoken feedback as part of the teacher – student dialogue in classroom interaction (i.e. feedback talk). Drawing on a discourse analysis approach we identified linguistic and rhetorical indicators of feedback talk and found a number of common patterns in six seminar events. Interviews with two teachers revealed a perception that feedback was an inherent part of the teaching and learning process and agreement on the significance of feedback talk in supporting relationships. We argue that a recognition and understanding of feedback talk can support the relational dimension of feedback literacy in the micro-moments of learning and teaching. We frame our discussion of feedback talk and teacher feedback literacy within the wider context of learning and teaching and call for a more holistic perspective on feedback.